A Comparative Study of Unfolding of Erythrina cristagalli Lectin in Chemical Denaturant and Fluoroalcohols - Sen, Debasish; K. Mandal, Dipak (Protein and Peptide Letters, 2014)
The unfolding of dimeric Erythrina cristagalli lectin (ECL) has been investigated and compared under different denaturing conditions in presence of chemical denaturant, guanidine hydrochloride (GdnHCl) and fluoroalcohols, trifluoroethanol (TFE) and hexafluoroisopropanol (HFIP). The GdnHCl-induced unfolding exhibits three-state mechanism involving structured intermediate that corresponds to tertiary monomer. The intermediate has been characterized by 8- anilino-1-naphthalenesulfonate (ANS) binding, which shows 30 fold increase in ANS fluorescence and selective chemical modification with N-bromosuccinimide when Trp 45 and Trp 207 are possibly oxidized. The results are supported by red edge excitation shift (10 nm), acrylamide quenching and phosphorescence studies which give a (0,0) band at 412.6 nm. TFE and HFIP show differing roles and characteristics of ECL unfolding. In TFE, but not in HFIP, a molten globulelike monomeric intermediate is formed, being characterized by ANS binding and concentration dependent studies. TFEand HFIP-induced secondary structure changes of ECL, as monitored by far-UV CD, show that conversion of β-sheet to α-helix occurs at lower HFIP concentration compared to TFE perturbation, helical content reaching to 65 % in 80 % HFIP and 53 % in 90 % TFE. Temperature-dependent studies reveal that induced helix entails reduced thermal stability. FTIR results show partial β-sheet to α-helix conversion but with quantitative yield. The tryptophan environment of TFE- and HFIP-induced states is dissimilar involving oxidation of four and three tryptophans respectively, and also differs from the fully unfolded state in GdnHCl when all five tryptophans undergo oxidation. The results offer insights into the unfolding problem of ECL.
Keywords: oligomeric protein